Case-control study of anthropometric measures and testicular cancer risk - Giannandrea, Fabrizio; Paoli, Donatella; Lombardo, Francesco; Lenzi, Andrea; Gandini, Loredana (Frontiers in Endocrinology, 2012)
The etiology of testicular germ cell tumors (TGCTs) is poorly understood. Recent epidemiological findings suggest that TGCT risk is determined very early in life, although the available data are still conflicting. The rapid growth of the testes during puberty may be another period of vulnerability. Body size has received increasing attention as possible risk factor for TC. To clarify the relation of body size and its anthropometric variables to TGCT risk, the authors analyzed data from 272 cases and 382 controls with regard to height (cm), weight (Kg) and body mass index (BMI; kg/m2). Overall, participants in the highest quartile of height were more likely to be diagnosed with TGCTs than participants in the lowest quartile of height, OR 2.22 (95% confidence intervals (CI): 1.25-3.93; adjusted; ptrend = 0.033). Moreover, histological seminoma subgroup was significantly associated with tallness, very tall men (>182 cm) having a seminoma TGCT risk of OR=2.44 (95% confidence intervals (CI): 1.19-4.97; adjusted; ptrend = 0.011). There was also a significant inverse association of TGCT with increasing BMI (ptrend = 0.001; age-adjusted analysis) and this association was equally present in both histological subgroups. These preliminary results indicate that testicular cancer is inversely associated with BMI and positively associated with height, in particular with seminoma subtype. Several studies have reported similar findings on body size. As adult height is largely determined by high-calorie intake in childhood and influenced by hormonal factors at puberty, increased attention to postnatal exposures in this interval may help elucidate the etiology of TGCTs.